2020
DOI: 10.1016/j.matlet.2019.127121
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous anodization/anaphoretic electrodeposition synthesis of nano calcium phosphate/titanium oxide composite coatings assisted with chitosan oligosaccharide lactate

Abstract: Ignjatović, Simultaneous anodization/anaphoretic electrodeposition synthesis of nano calcium phosphate/titanium oxide composite coatings assisted with chitosan oligosaccharide lactate, Materials Letters (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 19 publications
(21 reference statements)
3
30
0
Order By: Relevance
“…Calcium phosphates (CP), amongst which amorphous calcium phosphate (ACP) and hydroxyapatite (HAp), along with TiO2 layers on Ti, have found vast applications in preventive and regenerative medicine due to their excellent biocompatibility, nontoxic properties and ability to participate in the normal metabolism of organisms. [1][2][3][4][5][6][7] New research on chitosan oligolactate (ChOL) coated HAp particles for drug delivery have indicated the advanced properties of this derivative. 4 The authors have already published the results about synthesis, physicochemical and bioactive properties of new ACP and ChOL-based multifunctional hybrid composite materials by novel in situ anodization/anaphoretic process.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Calcium phosphates (CP), amongst which amorphous calcium phosphate (ACP) and hydroxyapatite (HAp), along with TiO2 layers on Ti, have found vast applications in preventive and regenerative medicine due to their excellent biocompatibility, nontoxic properties and ability to participate in the normal metabolism of organisms. [1][2][3][4][5][6][7] New research on chitosan oligolactate (ChOL) coated HAp particles for drug delivery have indicated the advanced properties of this derivative. 4 The authors have already published the results about synthesis, physicochemical and bioactive properties of new ACP and ChOL-based multifunctional hybrid composite materials by novel in situ anodization/anaphoretic process.…”
Section: Introductionmentioning
confidence: 99%
“…4 The authors have already published the results about synthesis, physicochemical and bioactive properties of new ACP and ChOL-based multifunctional hybrid composite materials by novel in situ anodization/anaphoretic process. [1][2][3] However, in order to complete the research, there was need for in vitro cytotoxicity tests of the obtained materials, in order to elucidate their *Corresponding author: mpavlovic@tmf.bg.ac.rs; Phone: +381 11 3640 231 https://doi.org/10.2298/JSC210211024P O n L i n e F i r s t biomedical compatibility. This note aims to report the cytotoxicity analysis to round out the research on the novel materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations